Synergistic virulence of Porphyromonas gingivalis and Treponema denticola in a murine periodontitis model - Orth, R.K-H.; O'Brien-Simpson, N.M.; Dashper, S.G.; Reynolds, E.C. (Molecular oral microbiology, 2011)
Summary Chronic periodontitis is characterized by the destruction of the tissues supporting the teeth and has been associated with the presence of a subgingival polymicrobial biofilm containing Porphyromonas gingivalis and Treponema denticola. We have investigated the potential synergistic virulence of P. gingivalis and T. denticola using a murine experimental model of periodontitis. An inoculation regime of four intra‐oral doses of 1 × 1010P. gingivalis cells induced significant periodontal bone loss compared with loss in sham‐inoculated mice, whereas doses of 1 × 109 cells or lower did not induce bone loss. Inoculation with T. denticola with up to eight doses of 1 × 1010 cells failed to induce bone loss in this model. However, four doses of a co‐inoculum of a 1 : 1 ratio of P. gingivalis and T. denticola at 5 × 108 or 1 × 109 total bacterial cells induced the same level of bone loss as four doses of 1 × 1010P. gingivalis cells. Co‐inoculation induced strong P. gingivalis‐specific T‐cell proliferative and interferon‐γ‐dominant cytokine responses, and induced a strong T. denticola‐specific interferon‐γ dominant cytokine response. Only at the higher co‐inoculum dose of 1 × 1010 total cells was a T. denticola‐specific T‐cell proliferative response observed. These data show that P. gingivalis and T. denticola act synergistically to stimulate the host immune response and to induce alveolar bone loss in a murine experimental periodontitis model.